ASPECTS OF THE EVOLUTION OF HUMAN RIGHTS PROTECTION IN THE EUROPEAN UNION - NICOLAE PURDĂ (Challenges of the Knowledge Society)
Human rights protection within the European Community and the European Union has developed judicially, the human rights being protected by the Community Courts as general principles of Community law. The Treaty of Maastricht and the Treaty of Amsterdam have codified the Community law within the area of human rights. The codification of European Union’s concept of human rights in a single document was realized by adopting the Charter of Fundamental Rights of the European Union, on 7 December 2000 in Nice, whose provisions acquired legally binding under the Treaty of Lisbon.